Investigating the perceived university support and the relationship between entrepreneurship education and self-employment intention - Asmaul Husna, Haris Fadzilah; Wan Mohd Hirwani, Wan Hussin (Society of Business and Management, 2021)
Currently, Malaysia is being faced with a high rate of unemployment among the graduates emerging from the higher educational institutions. This is one of the main social development problems facing by the Malaysian government. Graduates preference for paid employment over self-employment intention is one of the contributing factors to this current problem. The roles of universities promoting entrepreneurship education and entrepreneurial skills to the students are increasing. This study is to analyse to moderate factor of university support to the relationship between entrepreneurship education and self-employment intention. Several studies were selected for review, the findings of the study are supported by the application of relevant theories. The findings of this study can be used as a reference for future researchers to get an initial picture related to this issue.